Novel insights into mechanisms of inhibition of colonic motility by loperamide - Parkar, Nabil; Spencer, Nick J.; Wiklendt, Luke; Olson, Trent; Young, Wayne; Janssen, Patrick; McNabb, Warren C.; Dalziel, Julie E. (Frontiers in Neuroscience, 2024)
Background: It is well known that opiates slow gastrointestinal (GI) transit, via suppression of enteric cholinergic neurotransmission throughout the GI tract, particularly the large intestine where constipation is commonly induced. It is not clear whether there is uniform suppression of enteric neurotransmission and colonic motility across the full length of the colon. Here, we investigated whether regional changes in colonic motility occur using the peripherally-restricted mu opioid agonist, loperamide to inhibit colonic motor complexes (CMCs) in isolated mouse colon.Methods: High-resolution video imaging was performed to monitor colonic wall diameter on isolated whole mouse colon. Regional changes in the effects of loperamide on the pattern generator underlying cyclical CMCs and their propagation across the full length of large intestine were determined.The sensitivity of CMCs to loperamide across the length of colon varied significantly. Although there was a dose-dependent inhibition of CMCs with increasing concentrations of loperamide (10nM-1µM), a major observation was that in the mid and distal colon, CMCs were abolished at low doses of loperamide (100 nM), while in the proximal colon, CMCs persisted at the same low concentration, albeit at a significantly slower frequency. Propagation velocity of CMCs was significantly reduced by 46%. The inhibitory effects of loperamide on CMCs were reversed by naloxone (1µM). Naloxone alone did not change ongoing CMC characteristics.The results show pronounced differences in the inhibitory action of loperamide across the length of large intestine. The most potent effect of loperamide to retard colonic transit occurred between the proximal colon and mid/distal regions of colon. One of the possibilities as to why this occurs is because the greatest density of mu opioid receptors are located on interneurons responsible for neuro-neuronal transmission underlying CMCs propagation between the proximal and mid/distal colon. The absence of effect of naloxone alone on CMC characteristics suggest that the mu opioid receptor has little ongoing constitutive activity under our recording conditions.